Study of Effective Corridor Design to Improve Wayfinding in Underground Malls - Zhang, Shaoqing; Park, Soobeen (Frontiers in Psychology, 2021)
In retail space, wayfinding difficulties can cause problems, such as loss of time, stress, or discomfort, negatively affecting the consumers’ shopping experience and even their patronage intentions. While studies have reported that space configuration may facilitate navigation, there has been a lack of detailed discussion, particularly in underground malls, where people often encounter wayfinding issues. In this study, a series of exit-finding tasks in virtual malls were simulated to determine if it was practical to encourage turn taking by changing the corridor width, length, height, or angle. The results showed that people have a right-turn preference during exit finding. Moreover, exit-finders mostly prefer taking the upward pathway via stairs followed by corridors with broader widths or curved corners, exhibiting visible and similar navigation effects. Shorter corridors have a visible but relatively small affinity. This study provides some empirical evidence of how the corridor configuration influences people’s turn taking and provides a theoretical reference for adding a guiding function to the spatial arrangement in underground malls.